Shaping scientific excellence in agricultural research. (9th April 2007) - Chataway, Joanna; Smith, James; Wield, David
Science and technology and particularly biotechnology is increasingly central to development agendas in Africa and elsewhere. Implicit within the centrality of science and technology lie a set of policy issues regarding how best to shape contextually appropriate, innovative and sustainable science and technological products in, with and for developing countries. The work of the Consultative Group on International Agricultural Research (CGIAR) is a case in point and we draw our empirical material from the evolution of two biotech bovine vaccine development programmes housed in a CG Centre. In the paper, we seek to show that broadening our understanding of scientific 'excellence' can lead to more innovative, systemic research that may produce more appropriate technological solutions. We believe this has key implications for science policy, development policy and the practice of science for development itself.